Post-traumatic Stress Symptoms and Serotonin Transporter (5-HTTLPR) Polymorphism in Breast Cancer Patients - Zerbinati, Luigi; Murri, Martino Belvederi; Caruso, Rosangela; Nanni, Maria Giulia; Lam, Wendy; De Padova, Silvia; Sabato, Silvana; Bertelli, Tatiana; Schillani, Giulia; Giraldi, Tullio; Fielding, Richard; Grassi, Luigi (Frontiers in Psychiatry, 2021)
Introduction: Post-traumatic Symptoms (PTSS) and Post-traumatic Stress Disorder (PTSD) have been reported to affect a quite significant proportion of cancer patients. No study has examined the relationship between serotonin transporter gene-linked polymorphic region (5-HTTLPR) and cancer, including Gene-Environment interactions between this polymorphism and specific causes of distress, such as cancer related problems (CRP) or life stressful events (SLE). Methods: One hundred and forty five breast cancer outpatients participated in the study and were assessed using the Impact of Event Scale (IES), the Problem List (PL) developed by the National Comprehensive Cancer Network (NCCN) Distress Management Guidelines and the Paykel's Life Events Interview to evaluate the exposure to SLE during the year before the cancer diagnosis. Each patient was genotyped for 5-HTTLPR polymorphism by analyzing genomic DNA obtained from whole blood cells. Gene-Environment interactions were tested through moderation analysis. Results: Twenty-six patients (17.7%) were classified as PTSS cases using the IES. Genotype and phenotype distributions did not differ across individuals with/without PTSS (genotype: χ2 = 1.5; df = 2; p = 0.3; phenotype χ2 = 0.9; df = 1; p = 0.2). For both the genotype and phenotype model, using CRP as a predictor showed significant gene-environment interactions with IES total score (p = 0.020 and p = 0.004, respectively), with individuals carrying the l/l allele showing a greater probability of experiencing PTSS. No interaction was found in relationship to SLE (p = 0.750). Conclusion: This study showed a significant GEI between CRP and PTSS in breast cancer patients, with carriers of the l/l allele showing indicators consistent with greater sensitivity to stress.